Lower Airway Microbiota - Pulvirenti, Giulio; Parisi, Giuseppe Fabio; Giallongo, Alessandro; Papale, Maria; Manti, Sara; Savasta, Salvatore; Licari, Amelia; Marseglia, Gian Luigi; Leonardi, Salvatore (Frontiers in Pediatrics, 2019)
In the last several years, the interest in the role of microbiota in human health has grown significantly. For many years, the lung was considered a sterile environment, and only recently with more sophisticated techniques, has it been demonstrated that colonization by a complex population of microorganism in lower airways also occurs in healthy subjects with the predominance of some species of Proteobacteria, Firmicutes, and Bacteroidetes phyla and with a peculiar composition in some disease conditions, such as asthma. Lung microbiota derives mainly from the higher airways microbiota. Although we know something about the role of gut microbiota in modulation of immune system, less it is known about the connection between lung microbiota and local and systemic immunity. There is a correlation between altered microbiota’s composition and some diseases or chronic states; however, despite this correlation, it has not been clearly demonstrated if the lung microbiota dysbiosis could be a consequence or a cause in these diseases. We are far from a scientific approach in the therapeutic use of probiotics in airway diseases, but we are only at the starting point of a knowledge process in this fascinating field that could reveal important surprises, and randomized prospective studies in future could reveal more about the clinical possibilities to control lung microbiota. This review is aimed at updating the current knowledge in the field of airway microbiota.